2023
DOI: 10.1021/acsaem.3c01025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoroethylene Carbonate Electrolyte Additives on the Electrochemical Performance of Nickel-Rich NCM Ternary Cathodes

Abstract: It has been well established recently that fluorinated electrolyte additives such as fluoroethylene carbonate (FEC) could promote the formation of LiF-based solid electrolyte interphases that can stabilize lithium metal anodes. Meanwhile, the impact of FEC additives on the cathode side, particularly for the high energy density nickel-rich LiNi1–x–y Co x Mn y O2 (NCM) ternary cathodes, remains unclear. In this study, we investigated the structural and chemical composition of a cathode electrolyte interphase (CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Another approach is the in situ construction of the cathode–electrolyte interface (CEI) through the addition of certain additives. For example, carbonate (FEC), tributyl borate (TBB), and adiponitrile have been used as additives to facilitate the formation of a protective CEI layer. This approach improves the stability of the CEI and enhances the cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is the in situ construction of the cathode–electrolyte interface (CEI) through the addition of certain additives. For example, carbonate (FEC), tributyl borate (TBB), and adiponitrile have been used as additives to facilitate the formation of a protective CEI layer. This approach improves the stability of the CEI and enhances the cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that 3-(trifluoromethyl)­benzoylacetonitrile can be preferentially oxidized to form a stable and dense CEI film, which inhibits the continuous oxidation and decomposition of the electrolyte, thereby safeguarding the structural integrity of NCM811 particles. She et al revealed that the addition of FEC can promote the formation of LiF-rich CEI films, which helps to stabilize the cathode at a lower rate and low cutoff voltage. However, the decomposition of both LiPF 6 and FEC at a higher rate and higher voltage could form thick LiF-rich CEI films that hindered Li + migration, leading to higher polarization and lower capacity retention.…”
Section: Introductionmentioning
confidence: 99%